Is it Good to Have Options? The 2014 Farm Bill Program Decisions. (13th November 2017) - Taylor, Mykel R; Tonsor, Glynn T; Paulson, Nicholas D; Ellison, Brenna; Coppess, Jonathan; Schnitkey, Gary D
Abstract: The 2014 Farm Bill continued the trend towards more risk management‐based support for U.S. farmers. However, it also represents a major departure from previous legislation by introducing multiple program options among which producers had the ability to choose. While allowing producers to have choices creates flexibility, the design of the program required producers to consider potential outcomes for crop prices and production levels in future periods when making their decisions. Experience over the first two years of program implementation suggests that while programs are working as designed, not all producers are fully satisfied with their enrollment decisions. This will lead to proposals for further modification to programs, and to questions about whether program choice should be a component of the next Farm Bill.